Trabalho, sociedade e marxismo: uma abordagem comparada do trotskismo no Brasil e nos Estados Unidos dos anos 1930 - Lisboa, Roberto Borges (2019)
This paper presents a study of the Trotskyist agency and its theoretical and political elaborations in Brazil and the United States of the 1930s. In this sense, it involves the political organizations led by the Bolshevik leader Leon Trotski in their variations in the referred period, involving the their political interactions as Left Opposition, when they recognize themselves as a legitimate fraction of their respective communist parties, as parties themselves by the construction of a new international and, finally, as parties of the IV International. In the meantime, the Trotskyists elaborated theoretically and politically from their respective social formations and, nevertheless, using Trotsky's theoretical and political framework, sought to understand them, but without losing sight of their relations with capitalist development at the time of imperialism. Incidentally, this was the central argument for the writing of this thesis. Also, the present paper sought to understand how Trotskyists viewed Roosevelt and Vargas governments' labor and union legislation to highlight and problematize their connections with the worlds of labor, in a period marked by two central episodes for both countries, the Great Depression, mainly, in the USA, and the government emerged from the so-called "Revolution of 1930" and its subsequent evolution. Finally, this work was done in the Pos-Graduate Program in History, Federal University of Santa Maria (UFSM, RS) and is linked to the research line "Culture, Migrations and Work".